Differential marking of excision planes in screened breast lesions by organically coloured gelatins. - Armstrong, J S (1990)
Traditionally India ink has been used to mark surgical resection margins, more recently with acetone to aid drying. Alternative methods have been suggested in recent months, including solutions of alcian blue, and Tippex. These methods use one colour only and Tippex is radiodense. Artists' pigments have been used, but their radiodensity makes them unsuitable for the detailed mammograms of the sliced screened specimens. An alternative method was specifically designed for impalpable breast lesions. It is based on coloured gelatins that are painted on to the biopsy specimen before dissection. The markers are radiolucent, quick to set, and do not penetrate the connective tissue. They can be applied to both fresh and fixed tissues, and the cost is about 0.05 pounds a specimen. The system is also suitable for marking other large specimens.